Association of TCM body constitution with insulin resistance and risk of diabetes in impaired glucose regulation patients - Hong You; Tong Zhang; Wen Feng; Yun Gai (BMC, 2017)
Abstract Background Impaired glucose regulation (IGR) patients have increased risk of type 2 diabetes mellitus (T2DM). Identifying relevant risk factors in IGR subjects could facilitate early detection and prevention of IGR progression to diabetes. This study investigated the association between Traditional Chinese Medicine (TCM) body constitution and serum cytokines, and whether body constitution could independently predict diabetes in IGR subjects. Method Patients with IGR (n = 306) received a blood test and their body constitution type was assessed using a body constitution questionnaire (BCQ). Serum levels of cytokines were measured by ELISA. Patients were followed up for at least three years, and their status of diabetes were recorded. Multivariate logistic regression was used to estimate odds ratios (ORs) of diabetes for body constitution. Results Phlegm-damp, Damp-heat and Qi-deficiency were three most common unbanlenced constitutions among IGR subjects. Phlegm-damp and Damp-heat constitution subjects showed higher serum levels of interleukin 6 (IL-6), tumour necrosis factor-α (TNF-α), leptin and lower serum levels of adiponectin (P<0.05). Qi-deficiency constitution subjects showed higher serum levels of leptin and lower serum levels of adiponectin, glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) (P<0.05). Subjects with Phlegm-damp or Damp-heat constitution demonstrated a significantly higher risk of diabetes (P<0.05). Conclusion Phlegm-damp and Damp-heat TCM body constitution are strongly associated with abnormal serum cytokines, and could potentially serve as a predictor of diabetes in IGR subjects. Body constitution can help to identify IGR subjects who are at a high risk of progression to diabetes.